Comparative mammalian choline metabolism with emphasis on the high-yielding dairy cow. Issue 2 (19th February 2013) - Pinotti, L; Baldi, A; Dell'Orto, V
Abstract: The present review examines the importance of choline in dairy cow nutrition. Choline is an essential nutrient for mammals when excess methionine and folate are not available in the diet. The requirement for choline can be met by dietary choline and by transmethylation reactions. Two types of functions for choline are known: functions of choline per se ; functions as a methyl donor. The two principal methyl donors in animal metabolism are betaine, a metabolite of choline, and S-adenosyl-methionine, a metabolite of methionine. Choline and methionine are interchangeable with regard to their methyl group-furnishing functions. In adult ruminants, choline is extensively degraded in the rumen; for this reason dietary choline contributes insignificantly to the choline body pool and methyl group metabolism is generally conservative with a relatively low rate of methyl catabolism and an elevated rate of de novo synthesis of methyl groups via the tetrahydrofolate system. In dairy ruminants, the dietary availability of choline is still low, but the output of methylated compounds in milk is high, and precursors from the tetrahydrofolate pathway are limiting, especially at the onset of lactation. Therefore choline may be a limiting nutrient for milk production in high-yielding dairy cows.